2012
DOI: 10.3354/ab00449
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between algal abundance, environmental variables and sponge distribution patterns on southern hemisphere temperate rocky reefs

Abstract: Sponges are important components of temperate rocky reefs whose abundance and diversity are influenced by a range of biological and physical factors. In high light environments, sponges are generally less abundant and are often restricted to shaded microhabitats. However, this generalisation stems primarily from research conducted in the northern hemisphere, with comparatively little information from the southern hemisphere. The aim of the present study was to examine correlations between sponge abundance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Coralline and fleshy algae were more abundant on inclined surfaces, while invertebrate abundance (mainly as sheet-like growth forms) was higher on overhangs, which is consistent with previous studies from other latitudes (Logan et al 1984;Sebens 1985;Baynes 1999;Bell and Barnes 2000b;Miller and Etter 2011;Cárdenas et al 2012). Recently, Laudien and Orchard (2012) found distinct assemblages between inclinations in the shallows (until 30 m) but not in deeper zones (200 m) in Arctic sublittoral communities.…”
Section: Discussionsupporting
confidence: 88%
“…Coralline and fleshy algae were more abundant on inclined surfaces, while invertebrate abundance (mainly as sheet-like growth forms) was higher on overhangs, which is consistent with previous studies from other latitudes (Logan et al 1984;Sebens 1985;Baynes 1999;Bell and Barnes 2000b;Miller and Etter 2011;Cárdenas et al 2012). Recently, Laudien and Orchard (2012) found distinct assemblages between inclinations in the shallows (until 30 m) but not in deeper zones (200 m) in Arctic sublittoral communities.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research from rocky reefs in New Zealand has shown that a combination of inclination and abundance of canopy and turf-forming algae explained a large proportion of the variability in the distribution and abundance of sponges (Cárdenas et al, 2012). This study found that although most sponge species were negatively correlated with algal abundance, some species were positively correlated with the abundance of canopy-forming algae.…”
Section: Introductionmentioning
confidence: 71%
“…In those cases, it has been suggested that algal cover along with other depth‐related factors (such as hydrodynamism, sedimentation, light availability and substratum inclination) may influence sponge distribution patterns along a depth gradient (Preciado & Maldonado ; Cárdenas et al . ). Similarly, it has also been suggested that the dominance of algae over sponges in some areas may be because algae are strong competitors for space and their fronds can reduce the levels of light and water movement for sponges.…”
Section: Discussionmentioning
confidence: 97%
“…This kind of relationship has also been documented between sponge abundance and algal abundance in the northern (Preciado & Maldonado ) and southern (Cárdenas et al . ) hemisphere temperate rocky ecosystems. In those cases, it has been suggested that algal cover along with other depth‐related factors (such as hydrodynamism, sedimentation, light availability and substratum inclination) may influence sponge distribution patterns along a depth gradient (Preciado & Maldonado ; Cárdenas et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation